Critical Success Factors of Industrialized Building System (IBS) Implementation for Construction Industry in Yemen - Algumaei, Mohammed Saif; Sarpin, Norliana (Research in Management of Technology and Business, 2022)
The construction industry in Yemen is currently challengeable by political instability, economic and technical issues, and armed conflicts among local as a factors negatively influenced socio-economic development and produced a poor development of construction projects. However, implementing an effective construction method is highly required for improving the current poor construction development in Yemen. Therefore, Industrialized Building Systems (IBS) is an alternative solution for improving the Yemeni construction industry by implementing an effective technology to construct projects with good quality and reasonable cost. Thus, this study aimed to identify IBS benefits, investigate IBS implementation challenges, and study the Critical Success Factors (CSFs) of supporting IBS implementation. A quantitative approach was selected for conducting the study by distributing of online questionnaire survey among construction firms. For this study, the sample size was determined as 152 respondents, while only 49 contractors had completely responded online survey of this study with a responding rate of 32.23%. The primary findings showed that respondents have a proper awareness of IBS benefits including improving quality, saving time and cost, environment friendly, and flexibility of products designing. However, lack awareness and standards, poor readiness, cost related issues, and poor government supports are the main challenges that influence IBS implementation. Additionally, the study found clear guidelines, enhance knowledge and awareness, encourage and promote its implementation, capability of planning, controlling, and financing, and intensive trainings are CSFs that should be considered for a proper implementation of IBS and improving construction industry development in Yemen.